No Regional Disparities in Sofosbuvir Plus Ribavirin Therapy for HCV Genotype 2 Infection in Tochigi Prefecture and Its Vicinity - Watanabe, Shunji; Okamura, Yukishige; Yoshizumi, Hiroaki; Tahara, Toshiyuki; Imai, Masato; Kurata, Hidekazu; Numao, Norikatsu; Fukaya, Yukimura; Tano, Shigeo; Miura, Kouichi; Murayama, Kozue; Ozawa, Iwao; et al. (Internal Medicine, 2019)
Objective Regional disparities were observed in the outcomes of interferon (IFN)-based therapy for chronic hepatitis C virus (HCV) infection in a Japanese nationwide study. However, whether or not these regional disparities are observed in the outcomes of direct-acting antiviral drugs, including sofosbuvir (SOF) plus ribavirin (RBV) therapy, remains unclear. Methods We conducted a multicenter study to assess the efficacy of SOF plus RBV therapy for HCV genotype 2 infection in Tochigi Prefecture and its vicinity, in which IFN-based therapy yielded a low sustained virologic response (SVR) rate. In addition, we divided Tochigi Prefecture into six regions to examine regional disparities in the SVR. Patients We enrolled patients with chronic HCV genotype 2 infection. Results Of the 583 patients enrolled, 569 (97.6%) completed the treatment, and 566 (97.1%) also complied with post-treatment follow-up for 12 weeks. The overall SVR12 rate was 96.1% by per protocol and 93.7% by intention-to-treat analyses. No marked differences were observed in the SVR12 between subjects ≥65 and <65 years of age. Although large gaps were observed in the characteristics of patients and accessibility to medical resources, there was no significant difference in the SVR12 rate among the six regions in Tochigi Prefecture. Conclusion SOF plus RBV therapy was effective for HCV genotype 2 infection in an area where IFN-based therapy had previously shown unsatisfactory results. In addition, no regional disparities in the SVR12 were observed in Tochigi Prefecture.